Alaska, Nome, St. Joseph's Mission, 1930 - Hughes, William M.; Bureau of Catholic Indian Missions (e-Publications@Marquette, 1930)
The Bureau of Catholic Indian Missions (BCIM) was created in 1874 as the Office of the Commissioner for Catholic Indian Missions to protect, promote, and administer the Native American mission interests of the Catholic Church in the United States. Records in this group are organized by record group and then state or territory and year. Collection organization varies very little throughout the collection, however, prior to 1921, general correspondence was organized by location. Starting with Director Hughes, general correspondence was placed as its own subgroup within the collection and is organized alphabetically. Please go to Ask An Archivist if you have any questions.